VALUES AND VALORIZATION - Elena ANGHEL (Challenges of the Knowledge Society)
I live with the feeling that, in the past few years, Romania has been a drifting ship. We do not know where is it going, nor the place it will arrive at. Like any individual endowed with reason, I wonder why chaos took over this society and, if I would have the power to change anything, what would be the solution to less troubled waters. I think we lost our way because we forgot to always refer to the values that should guide us ... or because we refer too often to non-values. I think we could find our way and stop wandering if we will rely our evolution on values, if we will teach our children from a young age what values and non-values are and if we could run our existence in the spirit of a real value horizon. People live together, not just coexist, as so deeply professor Gheorghe Mihai highlighted1. Coexistence is specific to herds, packs, hordes; but human community means collaboration, cooperation, consensualisation, which implies a consciousness towards values. "What is missing now to the human society is a behavior that relates to a code of virtue"2. Moral values are the support for the legal values. Unfortunately, today, it seems to me that values are inverted and that the belief in the perfectibility of the individual (and therefore the perfectibility of law) is increasingly being questioned. Contemporary society is characterized by lack of motivation, lack of a strategy and the absence of any ideals. In this context, I believe that the individual today feels the necessity of some value referrences more acutely, whilst the society needs a law deeply based on moral values. As morality itself contributes to the valorization of the law, I think that moral appeal is more necessary today than yesterday, as a remedy for the individual and, consequently, the law to overcome their crisis. For all these reasons and also because I share the view that "the concrete law is not viable without values and these values are always expressed in the defining principles of a law system"3, I felt the need to write about values and valuation.